2012
DOI: 10.1590/s0102-36162012000200004
|View full text |Cite
|
Sign up to set email alerts
|

Osteossíntese da fratura do colo femoral: dois ou três parafusos?

Abstract: Objectives: To evaluate the efficacy of osteosynthesis on femoral neck fractures using two instead of three screws. Methods: Thirty-nine fractures were retrospectively evaluated, divided into groups in which two screws were used in parallel (n = 28) or three screws (n =11) in an inverted triangle configuration (in accordance with the AO technique). The patients were then followed up until reaching the outcome of either consolidation or failure. Results: In the group in which two screws were used, consolidation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
1
0
2
Order By: Relevance
“…However, some studies have shown that parallelism of the screws is not a foreseeable risk factor for complications, and these also do not mention the ability to stabilize the fracture with this synthesis methodology. 10 - 12…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have shown that parallelism of the screws is not a foreseeable risk factor for complications, and these also do not mention the ability to stabilize the fracture with this synthesis methodology. 10 - 12…”
Section: Discussionmentioning
confidence: 99%
“…Esse contexto possui grandes chances de mudar quando pacientes acima de 65 anos de idade são inseridos, apontados na Classificação de Garden como III ou IV. Devemos considerar que a classificação I refere-se a uma fratura incompleta; II é uma fratura completa sem desvio; III é fratura completa com desvio parcial; e na IV há um desvio completo da fratura 3 .…”
Section: Revisão Da Literaturaunclassified
“…A utilização de três desses itens na forma de um triângulo invertido se mostrou mais estável, apesar de que o uso de apenas dois parafusos também apresentou ser suficiente para o tratamento proposto. Não fosse o custo elevado, seu uso seria maior 3 .…”
Section: Abordagens E Localização Das Lesõesunclassified